Peroxisome Proliferator–Activated Receptor-α Agonism With Fenofibrate Does Not Suppress Inflammatory Responses to Evoked Endotoxemia - Mulvey, Claire K. (Blackwell Publishing Ltd, 2012)
BACKGROUND: Data conflict with regard to whether peroxisome proliferator–activated receptor-α agonism suppresses inflammation in humans. We hypothesized that in healthy adults peroxisome proliferator–activated receptor-α agonism with fenofibrate would blunt the induced immune responses to endotoxin (lipopolysaccharide [LPS]), an in vivo model for the study of cardiometabolic inflammation. METHODS AND RESULTS: In the Fenofibrate and omega-3 Fatty Acid Modulation of Endotoxemia (FFAME) trial, 36 healthy volunteers (mean age 26±7 years, mean body mass index 24±3 kg/m(2), 44% female, 72% white) were randomized to fenofibrate 145 mg or placebo daily. After 6 to 8 weeks of treatment, subjects underwent a low-dose LPS challenge. Clinical and blood measurements were collected at randomization, before LPS administration, and serially for 24 hours after LPS administration. We examined area under the curve for evoked responses by treatment group. Compared to placebo, but before LPS challenge, fenofibrate reduced total cholesterol and tended to decrease triglycerides, consistent with achieved therapeutic plasma levels of fenofibric acid. In the placebo group, LPS induced a modest inflammatory response with increased cytokines and chemokines (2- to 4-hour post-LPS 8-fold increase in tumor necrosis factor-α, 9-fold increase in interleukin-6, 9-fold increase in interleukin-10, and 10-fold increase in monocyte chemotactic protein-1; all P<0.001) and acute-phase reactants (24-hour post-LPS 15-fold increase in serum amyloid A and 9-fold increase in C-reactive protein; both P<0.001). Compared to placebo, however, fenofibrate did not significantly attenuate LPS-induced levels of plasma cytokines, chemokines, or acute-phase proteins. CONCLUSIONS: These data suggest a lack of systemic antiinflammatory properties of fenofibrate at clinically relevant dosing in humans. CLINICAL TRIAL REGISTRATION: URL: http://clinicaltrials.gov/ct2/show/NCT01048502. Unique identifier: NCT01048502. (J Am Heart Assoc. 2012;1:e002923 doi: 10.1161/JAHA.112.002923.)